Optimalisasi Promosi Usaha Mikro Penjahit dengan Papan Identitas dan Media Sosial - Agung, Banyu; Musleh, Musleh; Tari, Tari (Lembaga Publikasi Ilmiah Nusantara, 2025)
Micro sewing businesses have great potential in the creative industry, but they still face various challenges in enhancing their visibility and competitiveness. One of the main obstacles is the lack of effective promotional strategies. This study aims to optimize the promotion of micro sewing businesses through the use of identity boards and social media as marketing tools. The methods used include mentoring, training, and the implementation of digital marketing strategies for micro sewing business owners. The research findings show that the use of attractive and informative identity boards can improve brand awareness, while utilizing social media platforms such as Instagram and Facebook can expand marketing reach and enhance customer interaction. With the right promotional strategies, micro sewing businesses can become more well-known, acquire new customers, and increase sales revenue. The conclusion of this study emphasizes that the combination of strong visual identity and digital marketing is an effective step in strengthening the competitiveness of micro sewing businesses in the digital era.